The Role of Nuclear Phosphoinositides in the p53-MDM2 Nexus - Jeong Hyo Lee; Muhammad Khalil Salah; Xiangqin Chen; Nickolas Vladimir Kucherenko; Vincent L. Cryns; Richard A. Anderson (Cells)
Recent insights into the p53-MDM2 nexus have advanced deeper understanding of their regulation and potent impact on cancer heterogeneity. The roles of nuclear phosphoinositide (PIPns) in modulating this pathway are emerging as a key mechanism. Here, we dissect the molecular mechanisms by which nuclear PIPns stabilize p53 through the recruitment of small heat shock proteins (sHSPs), activate the nuclear phosphatidylinositol 3-kinase (PI3K)-AKT signaling cascade, and modulate MDM2 function to regulate the p53-MDM2 interaction. We propose potential mechanisms by which nuclear PIPns coordinate signaling with nuclear p53, AKT, and MDM2. Ultimately, we highlight that nuclear PIPns serve as a ‘third messenger’ within the p53-MDM2 axis, expanding the current framework of non-canonical nuclear signaling in cancer biology.